2015
DOI: 10.3928/23258160-20151008-05
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Anatomical and Functional Outcomes After Macular Hole Surgery: A Prospective, Controlled Study

Abstract: Eyes after MH repair demonstrated inferior RNFL and GCIPL thinning. Defect size in ELM, IS/OS junction, and COST line predicted visual recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…At 6 months, the nasal RNFL was significantly thicker in only the study by Hibi et al [ 14 ]. On the other hand, the inferior RNFL was reduced at 12 months as reported by Lalezary et al [ 18 ] or at 24 months by Thinda et al [ 27 ]. The inferior sector is the 226–315° quadrant with the Cirrus OCT.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…At 6 months, the nasal RNFL was significantly thicker in only the study by Hibi et al [ 14 ]. On the other hand, the inferior RNFL was reduced at 12 months as reported by Lalezary et al [ 18 ] or at 24 months by Thinda et al [ 27 ]. The inferior sector is the 226–315° quadrant with the Cirrus OCT.…”
Section: Discussionsupporting
confidence: 55%
“…It has been reported that the RNFL was thicker in the temporal sector at the baseline in eyes with an ERM and was thinner after successful surgery [ 24 ]. However, the RNFL thickness was evaluated in not only MH eyes but also some eyes with a MH and ERM in some studies [ 16 , 18 , 25 27 ]. We believe it is important to show that there was no significant difference in the preoperative RNFL thickness between the eyes with a MH and the fellow eyes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the etiology of IMH is varied and the exact mechanism of the development of IMH remains to be further explored, the consensus has not changed that the principle treatment for MH is vitreoretinal surgery. Currently, the classic procedure for treating IMH is pars plana vitrectomy with peeling of the internal limiting membrane and intraocular gas tamponade, followed by a face-down position for several days [ 4 , 5 ]. Because of gas tamponade, the face-down position after the IMH surgery can cause much discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…After the introduction of ILM peeling, the success rate of surgical management of macular hole has improved tremendously. Several studies have shown that internal limiting membrane (ILM) peeling in macular hole surgery causes changes in the macular thickness and decrease in retinal sensitivity [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%